Understand The Difference Between The Learning Process And Inspiration. Implications For Islamic Education Literature Review Of The Book Of Ihya Ulumuddin - Restu, Yanto Maulana; Deden Kurnia Adam; Wildan Mahmudin; Izzudin Musthafa; Ateng Ruhendi (IJGIE (International Journal of Graduate of Islamic Education), 2023)
The background to the problem is studying Imam al-Ghazali in the book Ihya Ulumuddin discussing the differences between the learning process and inspiration and the implications for Islamic education. The research methodology uses library research. The author applies theories from scriptures and books. The aim of this writing is to know the difference between the learning process and inspiration. The implications for Islamic education. The results obtained are that the learning process also explains that students in the learning process must have manners. Prioritizing mental cleanliness, Allah makes it easy for us to fulfill and apply the knowledge gained. Reducing worldly things. Don't be arrogant in seeking knowledge and don't argue with teachers. Avoid disputes between fellow humans, Not refusing to study a field of knowledge, Prioritizing the most important knowledge, namely the knowledge of the afterlife. Decorating the heart with qualities that convey it to Allah Ta'ala and. Inspiration means something that is whispered into the heart through the abundance of divine grace. The implications of Islamic education are efforts to form complete human beings, both in this world and in the afterlife. According to Al Ghazali, humans can achieve perfection if they are willing to try to seek knowledge and then practice fadhilah through the knowledge they learn.